Preparation of highly efficient Al-doped ZnO photocatalyst by combustion synthesis - Ahmad, M.; Ahmed, E.; Zhang, Yuewei; Khalid, N.R.; Xu, Jianfeng; Ullah, M.; Hong, Zhanglian (Current applied physics, 2013)
Novel Al-doped ZnO (AZO) photocatalysts with different Al concentrations (0.5–6.0 mol%) were prepared through a facile combustion method and followed by calcination at 500 °C for 3 h. The obtained nanopowders were characterized by powder X-ray diffraction (XRD), scanning electron microscope (SEM) combined with EDX, transmission electron microscope (TEM), Fourier transform infrared spectroscopy (FTIR), UV–vis spectroscopy and photoluminescence spectroscopy. The XRD patterns of AZO nanopowders were assigned to wurtzite structure of ZnO with the smallest crystallite size about 11 nm consistent with the results from TEM. The doping of Al in ZnO crystal structure successfully suppressed the growth of ZnO nanoparticles confirmed by XRD patterns. The absorption spectra analysis showed that the optical band gap energy (Eg) for the AZO nanopowders were in the range of 3.12–3.21 eV and decreased with increasing of Al dopant. The photocatalytic activities of the samples were evaluated by photocatalytic degradation of methyl orange under visible light (λ ≥ 420 nm) and sunlight irradiation. The results showed that the AZO photocatalyst doped with 4.0 mol% Al exhibited five times enhanced photocatalytic activity compared to pure ZnO. The enhanced photocatalytic activity could be attributed to extended visible light absorption, inhibition of the electron–hole pair's recombination and enhanced adsorptivity of MO dye molecule on the surface of AZO nanopowders. ► Successful synthesis of ZnO and Al doped ZnO (AZO) photocatalyst with high porosity by combustion method. ► Extended light absorption and efficient charge separation due to aluminum doping. ► Enhanced adsorptivity of MO dye on the catalyst surface. ► Photocatalytic activity enhancement of AZO photocatalyst over pure ZnO.